1982
DOI: 10.1111/j.1432-1033.1982.tb06675.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence that Cholesterol Ester Hydrolase from Adrenal Cortex is the Same Enzyme as Hormone‐Sensitive Lipase from Adipose Tissue

Abstract: Several properties of the cytosolic cholesterol ester hydrolase from bovine adrenal cortex were investigated and those properties were compared directly with those of the well-characterised hormone-sensitive lipase, the ratelimiting enzyme in adipose tissue lipolysis. Properties examined included : (a) activity against different substrates; (b) susceptibility to inhibition by NaF, Hg2+ ions and diisopropyl fluorophosphonate; (c) subunit molecular weight as determined by polyacrylamide gel electrophoresis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 25 publications
0
60
1
Order By: Relevance
“…The previously proposed function of HSL in steroidogenic tissues is the mobilization of free cholesterol for steroid biosynthesis [4,32,34,37]. However, the lack of expression of HSL in Leydig cells demonstrated in this study, together with the apparent lack of steroid hormone synthesis from cholesterol in Sertoli cells [38], seriously question this proposal, at least with regard to testis.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The previously proposed function of HSL in steroidogenic tissues is the mobilization of free cholesterol for steroid biosynthesis [4,32,34,37]. However, the lack of expression of HSL in Leydig cells demonstrated in this study, together with the apparent lack of steroid hormone synthesis from cholesterol in Sertoli cells [38], seriously question this proposal, at least with regard to testis.…”
Section: Discussioncontrasting
confidence: 51%
“…These stores are thought to be important for steroid biosynthesis and spermatogenesis [1][2][3][4][5]. Spermatogenesis is severely impaired by temperature elevation, and we have previously shown that experimental cryptorchidism in the rat leads to a decrease in testicular cholesterol esterase activity, concomitant with increased lipid accumulation in Sertoli cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hormone-sensitive lipase (HSL) present in the adrenal also acts as a cholesterol esterase, and lack of HSL activity significantly decreases ACTH-stimulated corticosterone production (7,18). HSL activity is modulated through hormonal/neuronal mechanisms (e.g., free fatty acid release from adipocytes).…”
Section: Discussionmentioning
confidence: 99%
“…The AMP-activated protein kinase would thus not only exert a feedback regulation of the synthesis of fatty acids (via phosphorylation of acetyl-CoA carboxylase) but also of their release from triglycerides. HSL has been shown to act as a hormone-sensitive, cholesterol-ester hydrolase in steroidogenic tissues, controlling the release of free cholesterol from intracellular stores of cholesterol esters [21,221. The AMP-activated protein kinase may therefore regulate both the synthesis of cholesterol (via phosphorylation of 3-hydroxy-3-methylglutaryl-CoA reductase) and its release from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%